The increase in hemoglobin concentration with altitude varies among human populations. Issue 1 (30th June 2019) - Gassmann, Max; Mairbäurl, Heimo; Livshits, Leonid; Seide, Svenja; Hackbusch, Matthes; Malczyk, Monika; Kraut, Simone; Gassmann, Norina N.; Weissmann, Norbert; Muckenthaler, Martina U.
Abstract: Decreased oxygen availability at high altitude requires physiological adjustments allowing for adequate tissue oxygenation. One such mechanism is a slow increase in the hemoglobin concentration ([Hb]) resulting in elevated [Hb] in high‐altitude residents. Diagnosis of anemia at different altitudes requires reference values for [Hb]. Our aim was to establish such values based on published data of residents living at different altitudes by applying meta‐analysis and multiple regressions. Results show that [Hb] is increased in all high‐altitude residents. However, the magnitude of increase varies among the regions analyzed and among ethnic groups within a region. The highest increase was found in residents of the Andes (1 g/dL/1000 m), but this increment was smaller in all other regions of the world (0.6 g/dL/1000 m). While sufficient data exist for adult males and females showing that sex differences in [Hb] persist with altitude, data for infants, children, and pregnant women are incomplete preventing such analyses. Because WHO reference values were originally based on [Hb] of South American people, we conclude that individual reference values have to be defined for ethnic groups to reliably diagnose anemia and erythrocytosis in high‐altitude residents. Future studies need to test their applicability for children of different ages and pregnant women. Abstract : The aim of our paper was to establish reference values for hemoglobin concentration ([Hb]) based on published data of residents living at different altitudes by applying meta‐analysis and multiple regressions. Results show that [Hb] is increased in all high‐altitude residents. However, the magnitude of increase varies among the regions analyzed and among ethnic groups within a region.